Leading lean by living lean : changing how you lead, not who you are - Holt, Philip (New York : Productivity Press, 2022)
In Leading Lean by Living Lean, Philip Holt details and explains what is probably the most important part of becoming a Lean Leader -- living and practicing what you preach. To do this you must believe in what you're doing, understand what it means and what you need to do, and do it every day. The author, through his engineering background, has fully embracedthe Plan-Do-Check-Act (PDCA) model of Deming / Shewhart but has adapted David Bovis' Believe-Think-Feel-Act (BTFA) model to understand why logic and facts are very often not the principal players in the game of change. In this book, Holt author describes how you can take both the PDCA and BTFA models into account and has sectioned the book into three prime parts: 1. Head -- How you learn and understand the Lean principles and their application. 2. Hands -- How you practice Lean Leadership daily. 3. Heart -- How you internalize and believe in Lean Leadership. Through this book, you, the Lean practitioner, whether aspiring or experienced, will have everything that you need to lead it, do it, and live it. The nature of this book is more why to than how to - the author knows that he cannot tell you how to lead, do, or live Lean; he can only explain why it is so important and share his knowledge, experiences, failures, and successes. This book isn't so much a self-help book as a self-reflection book and it can point you in the proper direction, but the book won't change you; only you can change you! Essentially, with this book, the author wants those who think of Lean as a toolkit, who believe that Lean can be project managed, or who argue about Lean versus Six Sigma and misunderstand the fundamental depth of impact that true Lean Leadership has on an organization to be disabused of any or all of those notions. This book is aimed at those leaders who seek to experience the full transformative effects of Lean in their organizations and want to practice it at the principle level of deployment. Holt's aim is to help business leaders enhance who they are by changing what they do and the way that they do it
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Lean manufacturing; Self-actualization (Psychology); BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Workplace Culture